ANALYSIS OF PROSPECTIVE TEACHER IN TROUBLE MASTERING BASIC SKILLS TEACHING - Siti Robiah ' (Biogenesis, 2015)
This study aimed to determine prospective teachers' difficulties in mastering the basic skills of teaching. The study population was a biology student of Class VI semester FKIP UIR D and E in Academic Year 2013/2014. which amounts to 87 people. This study starts from January to June 2014 while taking data from Februarit months to May 2014. Data analysis techniques used descriptive analysis techniques. Based on the results of data analysis can be seen that the prospective teachers are very experienced difficulty in mastering basic skills related to teaching in terms of Open Learning 72,98%, 77,03% Describes materials, difficulty in performing variation of 69,83%, 75,60% Skill asked, provide reinforcement of skills 67,28.67%, 70,58% class management skills, learning skills are close enough 53,67% . It can be concluded that the Prospective teachers have difficulty in mastering basic skills teaching teachers.Keywords : Analysis, Difficulty, Basic Skills Teaching